Reflection and Manifestations of Women in Literature: An Overview: Exploring the Restrictions and Empowerment of Women in Literature (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Literature is manifestation of our reality, which regardless of individual views it mirrors social manners, then women’s changing roles, be they emotional, social, and political, in literature and life must not to be buried. Though writings about females by males may be suspect, all literature, even women’s a writings about women may also need to be re-read. As Susan Carillon asserts in her essay, “The Fiction of Fiction, “Women internalize the male idea of the feminine and create themselves in the shape of that idea”. Women have held lightly to several role models as their guides. While male characters have been free reign to be and become what they like, even to fail if they choose, women characters have been written to play and replay the same themes, limited as they are. Women are forced to rise above being a woman.